Gender bias in urology: The role of gender in selecting urology as a medical specialty - Mansour Alnazari; Abdullah K. Aljohani; Emad S. Rajih; Abdulaziz Bakhsh; Ghadi S. Alghamdi; Faris S. Sebaa; Ali A. Alraddadi; Adel Moalwi (Urology Annals)
Background: Gender inequality has been prevalent in the history of medicine, specifically within surgical specialties. Although there have been advances, urology has remained overwhelmingly male-dominant, with slow growth in female recruitment. Objectives: The study aimed to assess whether the gender influences selection of medical specialty, especially gender bias in urology. Materials and Methods: A cross-sectional study was conducted among undergraduate medical students in Saudi Arabian medical schools to explore the influence of gender on urology specialty selection. Data were collected from November 2023 to June 2024 using a structured questionnaire administered electronically. A pilot study was conducted to evaluate the questionnaire’s reliability and clarity. Data were analyzed using descriptive and inferential statistics. The questionnaire demonstrated acceptable reliability. Results: The total study participants were 602 medical students. The dataset reveals a balanced gender representation, with males constituting 55.6% and females 44.4%. A substantial majority, 94.5%, expressed a definitive willingness to pursue further residency training following graduation, indicating a robust commitment to advancing their medical careers. However, while evaluating interest in urology, the statistics revealed a potential disparity, with only 43.2% affirmatively considering urology as a specialty, contrasted against 56.8% who would not. The study shows that the participants’ considering urology as a specialty has a statistically significant relation to gender (P = 0.0001) as 72.3% of those who would consider the specialty were males compared to only 27.7% for females. The data also show a concerning trend where 21.8% of those uninterested in urology reported insufficient exposure during medical school as a deterrent, while others found the specialty to be embarrassing or simply uninteresting, accounting for 70.8% of the negative responses. Conclusion: This study reveals a significant gender disparity in urology specialty selection among medical students. While the majority of students intend to pursue residency training, male students are significantly more likely to consider urology as a specialty compared to female students. Factors such as limited exposure and negative perceptions contribute to the underrepresentation of women in urology. Addressing these issues is crucial to achieving gender equality within the field.